Design and performance evaluation of precast wall panels made with GRG - Oliveira, Cláudia Terezinha de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper deals with the design of a partition panel made with composite matetial being the matrix gypsum (â hemihydrate) reinforced with ordinary E-glass chopped fibres. According to this research it was possible to select a composite with a fibre content of 2,25% by weight of hemihydrate and to use 13 mm long fibre, based on flexural tests and workability criteria. This componets presented 10,5 Mpa of flexural strenght. The components were procuced by volumetric method considered as a low cost method which requires non-skilled workers. Various geometric designs were proposed and panels performance evaluation were on the flexural and pull-out tests. The final panel design presented a 6,4 Mpa of flexural strength. This paper also presents the main results of mechanical and physical tests of GRG precast panel walls. The perfornance evaluation of walls was achieved by means of: resistance to soft body impact, operation of doors, suspension load bearing, resistence to slab deformation, dampeness resistence, sound insulation, tile coating adhesion.